Treatment Plan Technique and Quality for Single-Isocenter Stereotactic Ablative Radiotherapy of Multiple Lung Lesions with Volumetric-Modulated Arc Therapy or Intensity-Modulated Radiosurgery - Quan, Kimmen; Xu, Karen M.; Lalonde, Ron; Horne, Zachary D.; Bernard, Mark E.; McCoy, Chuck; Clump, David A.; Burton, Steven A.; Heron, Dwight E. (Frontiers in Oncology, 2015)
Purpose: The aim is to provide a practical approach to the planning technique and evaluation of plan quality for the multi-lesion, single-isocenter stereotactic ablative radiotherapy (SABR) of the lung. Methods and Materials: Eleven patients with 2 or more lung lesions underwent single-isocenter VMAT radiosurgery or IMRS. All plans were normalized to the target maximum dose. For each plan, all targets were treated to the same dose. Plan conformity and dose gradient were maximized with dose control tuning structures surrounding targets. For comparison, multi-isocenter plans were retrospectively created for 4 patients. Conformity index (CI), homogeneity index (HI), gradient index (GI) and gradient distance (GD) were calculated for each plan. V5, V10, and V20 of the lung and organs at risk (OARs) were collected. Treatment time and total monitor units (MUs) were also recorded. Results: One patient had 4 lesions and the remainder had 2 lesions. Six patients received VMAT and 5 patients received IMRS. For those treated with VMAT, two patients received 3-arc VMAT and four received 2-arc VMAT. For those treated with IMRS, two patients were treated with 10 and 11 beams, respectively, and the rest received 12 beams. Prescription doses ranged from 30 to 54 Gy in 3 to 5 fractions. The median prescribed isodose line was 84% (range: 80-86%). The median maximum dose was 57.1 Gy (range: 35.7-65.1 Gy). The mean combined PTV was 49.57 cm3 (range: 14.90 - 87.38 cm3). For single-isocenter plans, the median CI was 1.15 (range: 0.97-1.53). The median HI was 1.19 (range: 1.16-1.28). The median GI was 4.60 (range: 4.16-7.37). The median maximum radiation dose (Dmax) to total lung was 55.6 Gy (range: 35.7-62.0 Gy). The median mean radiation dose to the lung (Dmean) was 4.2 Gy (range: 1.1-9.3 Gy). The median lung V5 was 18.7% (range: 3.8-41.3%). There was no significant difference in CI, HI, GI, GD, V5, V10 and V20 (lung, heart, trachea, esophagus, and spinal cord) between single-isocenter and multi-isocenter plans. Conclusion: This multi-lesion, single-isocenter lung SABR planning technique demonstrated excellent plan quality and clinical efficiency and is recommended for radiosurgical treatment of 2 or more lung targets for well